2018
DOI: 10.29252/archhygsci.7.3.216
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation Optimal Ground Water Desalination Process with Membranes and Integrated Process Using AHP Method in Qom Province, Iran

Abstract: Background & Aims of the Study: Recently membranes have been widely used in Mena region especially Iran, due to purify the brackish water and solved the water scarcity. Qom province is located in desert like area of Iran and faced to water shortage. The aim of this study is evaluation of the best method of membrane process in the ground water wells of Qom province, Iran, in 2016. Materials and Methods: This descriptive cross sectional survey carried out at the central laboratory of water and Wastewater Company… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Naveed et al [13] used three and five decision-makers in AHP and Fuzzy-AHP and found having three decision-makers gave more accurate results whereas five decision-makers showed vagueness. Based on the literature review [13,17,18,170,171], three LDMs with more than five years' experience in membrane distillation were considered. One of the decision-makers is from the industrial field (desalination plant), and two are from the academic field.…”
Section: � ⊕mentioning
confidence: 99%
See 1 more Smart Citation
“…Naveed et al [13] used three and five decision-makers in AHP and Fuzzy-AHP and found having three decision-makers gave more accurate results whereas five decision-makers showed vagueness. Based on the literature review [13,17,18,170,171], three LDMs with more than five years' experience in membrane distillation were considered. One of the decision-makers is from the industrial field (desalination plant), and two are from the academic field.…”
Section: � ⊕mentioning
confidence: 99%
“…The inspection concluded that the highest technical and non-technical criteria were salt rejection and cost, respectively. Talaeipour et al [18] applied AHP to find the optimum desalination method for groundwater by comparing nano-filtration (NF), RO and hybrid NF/RO. The study found that the best performance was the hybrid NF/RO.…”
mentioning
confidence: 99%